Mediating effect of integrity on workplace spirituality and counterproductive work behaviours - Hashim, Junaidah (2012)
The objective of this research is to determine if and how spirituality is mediated by integrity which in turn influences organisation performance. Organisation performance is measured in term of the occurrence of counterproductive work behaviour. A total of 1203 employees of all levels from several prominent Islamic organisations in Malaysia responded to the questionnaires. Workplace spirituality was measured by a scale adopted from Petchsawang and Duchon (2009). Employees’ integrity was tested by using the Substance, Production loss, and Interpersonal Problem Inventory (SPI). It is a measure of overt integrity. Counterproductive work behaviour (CWB) measure was adapted from dimensionality of counterproductive work behaviour by Gruys and Sackett (2003). The results showed that the employees have moderate level of workplace spirituality and integrity. The findings revealed that the relationship between integrity and counterproductive work behaviour is very low and it is negative. This result supports integrity to partially mediate the relationship between workplace spirituality and counter-productive work behaviour. (156 words)